The long-term effects of cautious feed-in tariff reductions on photovoltaic generation in the UK residential sector (2020)
In recent years, the UK electricity sector has been seeking to achieve its environmental targets through subsidies to renewables. Although subsidies, through feed-in tariffs, to promote the adoption of photovoltaic (PV) systems by UK households had been successful, the government decided to significantly reduce these incentives. As these tariffs were precisely aimed to incentivise households to adopt PV systems, cutting those fees may have conflicted with the stated purpose of the policy, and its impact on industry participants is in turn uncertain. This paper seeks to contribute to the understanding of the long-term effects of cautious feed-in tariff reductions on household’s PV adoption, utilities and solar companies by considering a systems approach. This is important to ascertain counterintuitive effects. System Dynamics simulation, the chosen quantitative methodology in this paper, establishes that cutting subsidies to PV users could result in the reduction of PV installations and lower benefits for solar companies. Despite reductions in PV installations, this study finds that the market would still have potential for solar energy-related technology growth in the UK. For instance, lower feed-in tariffs are likely to promote the adoption of PV-battery systems to maximise self-consumption.